Educators' understanding of young children's typical and problematic sexual behaviour and their training in this area. Issue 6 (2nd November 2017) - Ey, Lesley-anne; McInnes, Elspeth; Rigney, Lester Irabinna
Abstract: As part of a wider study, this paper reports on Australian educators' understanding of children's typical and problematic sexual behaviour and their source of training in this area. A sample of 107 educators from government, independent and Catholic primary schools, preschools and care organisations across Australia answered an online questionnaire regarding their understanding of and experiences with children's problematic sexual behaviours and their management strategies. The majority of educators were able to identify children's age-appropriate typical sexual behaviour and some elements of problematic sexual behaviour; however, individual knowledge was not extensive. Approximately 35% ( n  = 35) of educators said they had not been trained in identifying and responding to children's problematic sexual behaviour. Of those who said they had received training, the majority (82%, n  = 53) described having participated in a compulsory course on reporting suspected abuse to government (a mandated reporting course). Ninety per cent ( n  = 89) of educators reported that courses specific to children's problematic sexual behaviours should be offered. This suggests that mandated reporting courses do not offer in-depth training specific to problematic sexual behaviour. Implications for professional development are discussed.